Hormone Use After Nonserous Epithelial Ovarian Cancer: Overall and Disease-Free Survival. Issue 5 (May 2016) - Power, Laura; Lefas, Georgia; Lambert, Pascal; Kim, Diane; Evaniuk, Debra; Lotocki, Robert; Dean, Erin; Nachtigal, Mark W.; Altman, Alon D.
Abstract : OBJECTIVE: To evaluate whether hormone therapy (HT) after nonserous epithelial ovarian cancer is associated with a decrease in overall and disease-free survival. METHODS: We conducted a retrospective cohort study. The Manitoba Cancer Registry and Drug Programs Information Network were searched to find all women with known nonserous epithelial ovarian, fallopian tube, or primary peritoneal cancer between 1995 and 2010 who had used HT after treatment. Women who did not receive treatment or had no follow-up were excluded. RESULTS: Three hundred ninety-one patients met the inclusion criteria. Seventeen patients were excluded because the patients did not receive treatment for cancer, and 17 were excluded for lack of follow-up. A total of 94 women received HT after treatment, and 263 women did not. The average age was 57.8 years. In HT users younger than 55 years of age, disease-free survival is improved according to both the multivariable landmark analysis (n=68/145, adjusted hazard ratio 0.354, 95% confidence interval [CI] 0.17–0.74, P =.006) and the time-varying Cox regression analysis (n=42/158, adjusted hazard ratio 0.212, 95% CI 0.07–0.60, P =.004) when adjusting for International Federation of Gynecology and Obstetrics stage and need for chemotherapy. There is no statistical difference in overall survival in this age group. No associations between HT use and overall survival or disease-free survival were found among women aged 55 years and older. CONCLUSION: After treatment for nonserous epithelial ovarian cancer, hormone therapy is not associated with decreased disease-free or overall survival. Abstract : After treatment for nonserous epithelial ovarian cancer, hormone therapy is not associated with decreased disease-free or overall survival.